Решите по образцу: а)-1+2+(-3)+5=(2+5)+((-1)+(-3))=7+(-4)=? б)-2+(-4)+2+5+(-3)+1+(-3)=? в)20+(-8)+2+5+(-10)+(-1)+(-3)=? г)-4+(-1)+3+(-2)+(-3)+9=? д)-17+17+(-8)+6+(-2)+8=? е)4+(-6)+(-1)+(-4)+6+(-3)+1=?

Решите по образцу: а)-1+2+(-3)+5=(2+5)+((-1)+(-3))=7+(-4)=? б)-2+(-4)+2+5+(-3)+1+(-3)=? в)20+(-8)+2+5+(-10)+(-1)+(-3)=? г)-4+(-1)+3+(-2)+(-3)+9=? д)-17+17+(-8)+6+(-2)+8=? е)4+(-6)+(-1)+(-4)+6+(-3)+1=?
Гость
Ответ(ы) на вопрос:
Гость
а)-1+2+(-3)+5=(2+5)+((-1)+(-3))=7+(-4)=3 б)-2+(-4)+2+5+(-3)+1+(-3)=2+5+1+((-2)+(-4)+(-3)+(-3)) = 8 + (-12) = -4 в)20+(-8)+2+5+(-10)+(-1)+(-3)=20+2+5+((-8)+(-10)+(-1)+(-3))= 27+(-22)=5 г)-4+(-1)+3+(-2)+(-3)+9=3+9+((-4)+(-1)+(-2)+(-3)=12+(-10)=2 д)-17+17+(-8)+6+(-2)+8=17+6+8+((-17)+(-8)+(-2))=31+(-27)=4 е)4+(-6)+(-1)+(-4)+6+(-3)+1=4+6+1+((-6)+(-1)+(-4)+(-3))=11+(-14)=-3
Не нашли ответ?
Ответить на вопрос
Похожие вопросы